The Road is Not an Event for Recklessness: The Effect of Emotion Regulation and Moral Disengagement on Driving Aggressiveness - Lesmana Nugraha, Luthfi; Nuqul, Fathul Lubabin (UIR Press, 2023)
The number of traffic accidents in Malang City in 2021 reached 159 reports from January to December 2021. This figure has increased by 30% compared to the previous year. As many as 36 people have died as a result of accidents. Traffic accidents often occur as a result of aggressive driving behavior such as reckless overtaking, anti-social behavior, and recklessness. Several studies have shown that aggressive driving behavior can be influenced by emotion regulation and moral restraint. This study aims to determine the effect of emotional regulation and moral restraint on aggressive behavior in motorcyclists in Malang City. This study uses a quantitative approach with multiple regression analysis methods. The subjects studied were 180 motorbike riders who live in Malang City. The results of the analysis show that the level of emotion regulation, moral mastery, and aggressiveness in motorcyclists in Malang City is at a moderate level. The results of the regression analysis show that there is an influence between emotional regulation and moral restraint on aggressive behavior in motorcyclists in Malang City. Simultaneously the variables of emotional regulation and moral pressure have a 28.8% effect on driving aggressiveness. In addition, aggressiveness in driving is also influenced by several factors, namely gender, age group, type of vehicle, and driving legality.